2022
DOI: 10.1002/saj2.20454
|View full text |Cite
|
Sign up to set email alerts
|

Cover crop monocultures and mixtures affect soil health indicators and crop yield in the southeast United States

Abstract: The southeastern United States has a long history of soil degradation due to intensive agriculture and climatic factors. Conservation management practices such as cover cropping aim to improve soil productivity and restore soil health. Our objectives were to evaluate the performance of cover crops and their short‐term effects on soil health indicators for two southeastern soil types. Cover crop experiments were conducted at the Wiregrass (WREC) and Tennessee Valley (TVREC) Research and Extension Centers in Ala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…(2022) was similar to the results in this experiment among cover crop systems. Under rainfed and irrigated practices in different environments, biomass production for different cover crop species and systems ranges from 438 to 12,000 kg DM ha −1 (Duiker, 2014; Nielsen et al ., 2015; Holman et al ., 2018; Haramoto, 2019; Decker et al ., 2022; Obour et al ., 2022). The results from our experiment under irrigation fall well within this range and indicate that with irrigation there is great potential for integrating cover crops in Nevada's semi-arid environment.…”
Section: Discussionmentioning
confidence: 99%
“…(2022) was similar to the results in this experiment among cover crop systems. Under rainfed and irrigated practices in different environments, biomass production for different cover crop species and systems ranges from 438 to 12,000 kg DM ha −1 (Duiker, 2014; Nielsen et al ., 2015; Holman et al ., 2018; Haramoto, 2019; Decker et al ., 2022; Obour et al ., 2022). The results from our experiment under irrigation fall well within this range and indicate that with irrigation there is great potential for integrating cover crops in Nevada's semi-arid environment.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the minimum amount of CC biomass required to alter labile SOC concentration is probably about 1 Mg ha −1 . The few individual studies assessing changes in labile SOC concentration under different levels of CC biomass production support this conclusion (Beehler et al, 2017;Decker et al, 2022;Ruis et al, 2017). The optimum amount of aboveground CC biomass needed to increase labile SOC concentration and improve other soil ecosystem services can be 4 to 7 Mg ha −1 , (Blanco-Canqui, 2022; Finney et al, 2016).…”
Section: Productionmentioning
confidence: 97%
“…In a temperate region, Singh et al (2021) measured impacts of cereal rye ( Secale cereale L.), hairy vetch ( Vicia sativa L.) and oat ( Avena sativa L.) + radish ( Raphanus sativus L.) CC treatments on both POXC and total SOC concentrations each year for 3 years and found that CCs had no effect on any C pool in any year compared with no CCs. Similarly, in a humid subtropical region, Decker et al (2022) measured impacts of rye, crimson clover ( Trifolium incarnatum L.), radish, and their mixes on both POXC and total SOC concentrations each year for 4 years in loamy sand and silt loam soils and found CCs had no effect on any C pool and year on the loamy sand and had mixed effects on the silt loam. Overall, the review results indicate CCs do not increase labile SOC more rapidly than total SOC concentration in all cases.…”
Section: Do Cover Crops Increase Labile C Concentration More Rapidly ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Legumes used as cover crops can also boost the availability of organic carbon and nitrogen (Balota et al., 2014; Verzeaux et al., 2016). Cover crops can have positive effects on multiple soil health indicators, but multi‐species cover crop mixes do not necessarily improve them better than one specie cover crop (Decker et al., 2022; Florence & McGuire, 2020; Reed & Morrissey, 2022). Moreover, cover crops can influence the soil microbiome.…”
Section: Introductionmentioning
confidence: 99%